2000
DOI: 10.1089/mdr.2000.6.231
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcus aureus:Phylogenetic Relatedness Between European Epidemic Clones and Swiss Sporadic Strains

Abstract: We have compared the phylogenetic diversity of methicillin-resistant Staphylococcus aureus (MRSA) strains from Switzerland and their phylogenetic relationships with European epidemic clones, using multiprimer random amplification polymorphic DNA (RAPD). Strains included 24 European epidemic clones (59 strains), 66 sporadic strains isolated in Switzerland in 1996-1997, and 15 reference strains of five other Staphylococcus species. Similarity and clustering analysis with the Jaccard's coefficient showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
1
21
1
Order By: Relevance
“…Both of these strains were shown to be closely related to the United Kingdom EMRSA-16 prototypic strain (data not shown), with both similar phage patterns when typed at SaRS and similar SmaI macrorestriction patterns. More recently, a Swiss strain (Geneva clone 2) related to EMRSA-16 was reported, with one isolate having originated in Greece (9). EMRSA-16 has also been identified in Norway (29), Spain (25), and the United States (21), where it is reported to be the second most common U.S. healthcare-associated pulsed-field type.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these strains were shown to be closely related to the United Kingdom EMRSA-16 prototypic strain (data not shown), with both similar phage patterns when typed at SaRS and similar SmaI macrorestriction patterns. More recently, a Swiss strain (Geneva clone 2) related to EMRSA-16 was reported, with one isolate having originated in Greece (9). EMRSA-16 has also been identified in Norway (29), Spain (25), and the United States (21), where it is reported to be the second most common U.S. healthcare-associated pulsed-field type.…”
Section: Discussionmentioning
confidence: 99%
“…), and related profiles were indicated by adding a number (A1, A2, B1, B2, etc). PFGE profiles of these strains were compared to a collection of European epidemic strains previously described (6). The type of the SCCmec was determined as previously described (38); selection of isolates was done in order to include for each year the first two to six isolates of each clone.…”
Section: Methodsmentioning
confidence: 99%
“…We used a typing method, multiprimer randomly amplified polymorphic DNA (RAPD), which was validated to produce information on the phylogenetic relationships between isolates (2).…”
mentioning
confidence: 99%
“…), and (iii) 12 Gen r and 8 Gen s strains isolated in 1996 and 11 Gen r strains isolated in 1990 from the National Reference Center for Staphylococcal Toxemia in Lyon, France. In addition, 24 strains isolated from other European countries were selected from a previous study and are representative of the diversity of MRSA observed (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation